Third World studies : theorizing liberation - Okihiro, Gary Y., 1945- (Duke University Press, 2016)
Gary Y. Okihiro presents the intellectual history of the core ideas, concepts, methods, and theories of Third World studies--an academic field first proposed in 1968 that never existed--in order to provide tools for understanding power and ending oppression.